2014
DOI: 10.3201/eid2008.140663
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of MERS Coronavirus from a Dromedary Camel, Qatar, 2014

Abstract: We obtained the full genome of Middle East respiratory syndrome coronavirus (MERS-CoV) from a camel in Qatar. This virus is highly similar to the human England/Qatar 1 virus isolated in 2012. The MERS-CoV from the camel efficiently replicated in human cells, providing further evidence for the zoonotic potential of MERS-CoV from camels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
159
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(166 citation statements)
references
References 15 publications
5
159
0
1
Order By: Relevance
“…To date, MERS-CoV has been detected in camels from Saudi Arabia, Oman, Qatar, Jordan and Kenya,7 8 10 19 20 and it has been shown that humans can acquire MERS-CoV directly from dromedary camels 21. Since camel exposure data (ie, whether the patient owned or raised camels) were gathered for only 204 of the 1250 cases in the database used by this study, we did not include this information in table 2.…”
Section: Discussionmentioning
confidence: 99%
“…To date, MERS-CoV has been detected in camels from Saudi Arabia, Oman, Qatar, Jordan and Kenya,7 8 10 19 20 and it has been shown that humans can acquire MERS-CoV directly from dromedary camels 21. Since camel exposure data (ie, whether the patient owned or raised camels) were gathered for only 204 of the 1250 cases in the database used by this study, we did not include this information in table 2.…”
Section: Discussionmentioning
confidence: 99%
“…5) and accessory proteins . At least nine MERS-CoV genomes harbour amino acid substitutions in the ribosome binding domain (RBD) of the spike protein and codons 158 (N-terminal region), 460 (RBD), 1020 (in heptad repeat 1), 1202 and 1208 bear investigation as markers of adaptive change (Cotten et al, 2014;Raj et al, 2014a). Studies are needed to determine whether there any functional outcomes on virus replication and transmission due to these and future changes (Cotten et al, 2014).…”
Section: Genomic Variability and Molecular Epidemiologymentioning
confidence: 99%
“…Camels have been acting as mixing vessels for viruses from different hosts (11,22), and they have been shown to have neutralizing antibodies against MERS-CoV (23-31). In camels testing positive for MERS-CoV, juvenile dromedary camels are often virus-positive, while older camels are more likely to be seropositive and virus-negative (25,27,(31)(32)(33). Serological studies have also indicated that camels can be the natural hosts of MERS-CoV infections, which were established long before the first human MERS-CoV cases were identified (26,28,34,35).…”
Section: Origin and Reservoir Of The Virusmentioning
confidence: 99%